A research synthesis of effective programs to address gender-based violence in the school context: actors involved, and impacts achieved - Molina Roldán, Silvia; íñiguez-Berrozpe, Tatiana; Renta-Davids, Ana Inés; Cerviño-López, Elsa (Frontiers in Education, 2025)
Gender-based violence is a social problem that is also present in schools. Scientific research on violence in the school setting has discussed schools as a context of socialization on gender violence, but also as a context where gender violence victimization can be prevented. Based on this, the objective of this study is to analyze and systematize the existing knowledge on effective programs addressing gender-based violence in school contexts (primary and secondary education) to identify the main components of effective programs and their key impacts. To this end, a research synthesis of the scientific literature was conducted. A total of 2,088 articles were initially retrieved from the primary scientific databases, and a final sample of 21 articles was analyzed after successive screening based on the inclusion criteria. Subsequently, the selected studies were analyzed according to the types of key actors involved in the programs studied and the impacts they informed. The results show, on the one hand, that there exist effective intervention programs that achieve positive impacts in preventing, reducing, and overcoming gender violence, which transform knowledge, attitudes, behaviors, and experiences related to gender violence. On the other hand, effective intervention programs are characterized by involving key actors, especially the peer group, teachers, and the community, which highlights the importance of promoting bystander intervention, effective teacher training, and community participation as a whole-school approach to effectively addressing gender-based violence in the school context.